2001
DOI: 10.1084/jem.193.2.207
|View full text |Cite
|
Sign up to set email alerts
|

Mice Lacking Expression of the Chemokines Ccl21-Ser and Ccl19 (plt Mice) Demonstrate Delayed but Enhanced T Cell Immune Responses

Abstract: The paucity of lymph node T cells (plt) mutation leads to a loss of CCL21 and CCL19 expression in secondary lymphoid organs. plt mice have defects in the migration of naive T cells and activated dendritic cells into the T cell zones of lymphoid organs, suggesting that they would have defects in T cell immune responses. We now demonstrate T cell responses in plt mice are delayed but ultimately enhanced. Responses to contact sensitization are decreased at day 2 after priming but increased at day 6. After subcuta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
169
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 166 publications
(190 citation statements)
references
References 44 publications
20
169
1
Order By: Relevance
“…Previous studies have shown that mice lacking CCL19/21 (paucity of lymph node T cells or plt) display delayed but enhanced immune responses (7,33,34). Whereas there is an altered pro-Th1-type inflammatory infiltrate in immunized plt LNs (34), other studies suggest that T-cell responses in these mice may be generated in the splenic red pulp or the cortex of the LN (7), potentially contributing to the enhanced responses observed.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies have shown that mice lacking CCL19/21 (paucity of lymph node T cells or plt) display delayed but enhanced immune responses (7,33,34). Whereas there is an altered pro-Th1-type inflammatory infiltrate in immunized plt LNs (34), other studies suggest that T-cell responses in these mice may be generated in the splenic red pulp or the cortex of the LN (7), potentially contributing to the enhanced responses observed.…”
Section: Discussionmentioning
confidence: 90%
“…Lymph node development and organization is accomplished mainly by the differential expression of CCL21 and CXCL13 in the T and B cell zones, respectively [62][63][64][65]. CCL21 and CXCL13 are ligands for CCR7 and CXCR5 (expressed by B cells), respectively, and are secreted by mesenchymal cells in the early developing lymph node to drive lymphoid tissue formation through the attraction of CD3ε − CD4 + IL-7Rα hi CCR7 + and CXCR5 + lymphoid tissue inducer cells [62,66].…”
Section: Secondary Lymphoid Organsmentioning
confidence: 99%
“…CCL19 is primarily expressed by LN Wbroblastic reticular cells (Chen et al 2002;Vassileva et al 1999;Weninger and von Andrian 2003). In mice that have a naturally occurring deletion of CCL21-Ser and CCL19 (paucity of lymph node T cells, plt/plt), DCs are capable of entering lymphatics in the skin, but accumulate in the superWcial cortex of draining LNs (Mori et al 2001).…”
Section: Chemokine Receptorsmentioning
confidence: 99%